Preparation method of wear-resistant coating on surface of planetary ball screw

By preparing Ti binding force layer, TiN transition layer and TiAlSiN nanocoating on the surface of the planetary ball screw, the problem of surface wear of the planetary ball screw is solved, and the wear-resistant coating with high strength and toughness and self-lubricating characteristics is achieved, and the planet is improved The wear resistance and service life of the ball screw.

CN119465057AInactive Publication Date: 2025-02-18BEIJING SCI & TECH PATENT OFFICE

Patent Information

Application Number
CN202510037637.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During long-term operation, the surface of the planetary ball screw will wear, which will affect the accuracy of the planetary ball screw.

Method used

A method for preparing a planetary ball screw surface wear-resistant coating is adopted, including substrate cleaning, ion cleaning, preparation of Ti binding force layer, preparation of TiN transition layer and preparation of TiAlSiN nanocoating. This method uses deep oscillating magnetron sputtering technology and composite pulsed DC magnetron sputtering technology to prepare a coating with high strength and toughness and self-lubricating characteristics.

Benefits of technology

The prepared wear-resistant coating has high nano hardness, good film-based bonding force, and fracture toughness, and has a low coefficient of friction. It is suitable for improving the wear resistance of planetary ball screws and extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465057A_ABST
    Figure CN119465057A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a wear-resistant coating on the surface of a planetary ball screw, and relates to the technical field of preparation of wear-resistant coatings. The preparation method of the wear-resistant coating on the surface of the planetary ball screw specifically comprises the following steps: S1, cleaning a substrate; s2, mounting a substrate; s3, ion cleaning is conducted, specifically, a glow cleaning process and a high-energy ion cleaning process are sequentially conducted for cleaning; s4, preparing a Ti binding force layer; s5, preparing a TiN transition layer; s6, a TiAlSiN nano coating is prepared; s7, sampling, wherein a sample is taken after 60-90 min after coating preparation is completed; the wear-resistant coating has the characteristic of integration of high strength and toughness, the prepared coating has high uniformity, and the process of the coating is flexible and adjustable. In addition, the pipe inner wall coating prepared through the method is high in deposition rate, easy and convenient to operate, low in cost and suitable for batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wear-resistant coating preparation, and in particular to a method for preparing a wear-resistant coating on the surface of a planetary ball screw. Background Art

[0002] As a special branch of threaded screw, planetary ball screw combines spiral and planetary motion. It is a low-friction precision transmission device that converts rotational motion into linear motion. Due to its complexity, ball screw is a relatively expensive drive (an order of magnitude more expensive than ball screw). Compared with ball screws of the same specifications, it has the characteristics of "compact structure, heavy load, high efficiency, high speed, and long life". It has high comprehensive performance and can be used in high-precision, high-speed, heavy-load, durable and heavy-use occasions. It has been used in high-tech fields such as aerospace, weapons and equipment, and nuclear power. At the same time, it also has a wide range of application needs in civilian scenarios such as machine tools, automotive ABS systems, and petrochemicals.

[0003] The linear joints of humanoid robots are the core components for achieving robot motion and action control, including planetary ball screws, flexible sensors, and intelligent encoders. Planetary ball screws are the core components of linear actuator joints, and their cost accounts for about 20% of the robot's cost. Planetary ball screws can maintain extremely high precision, quiet and smooth operation while producing minimal displacement, and overcome the inherent shortcomings of traditional hydraulic transmission devices such as "running, bubbling, leaking, and dripping", poor environmental adaptability, low reliability, and poor maintenance. They have been widely used in the field of robotics to replace hydraulic transmission devices in some scenarios.

[0004] During long-term operation, the surface of the planetary ball screw will wear, thereby affecting the accuracy of the planetary ball screw operation. Therefore, in order to ensure the high-precision operation and long-term maintenance-free of the linear joint, the present application prepares a wear-resistant self-lubricating coating on its surface to improve its wear resistance. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a wear-resistant coating on the surface of a planetary ball screw, which solves the problem that the surface of the planetary ball screw will be worn during long-term operation, thereby affecting the operating accuracy of the planetary ball screw.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing a wear-resistant coating on the surface of a planetary ball screw, specifically comprising the following steps: S1. Cleaning of substrate: Place the lead screw workpiece in a commercial degreasing cleaning agent container for ultrasonic cleaning for 20 to 30 minutes, then clean it with deionized water for 5 to 10 minutes, and then dry it and place it for later use; S2. Substrate installation: Open the vacuum chamber, place the cleaned lead screw workpiece on the sample platform, close the door and evacuate the vacuum until the vacuum degree is lower than 1×10 -4 Pa; S3, ion cleaning: cleaning by glow cleaning process and high energy ion cleaning process in sequence; S4, preparation of Ti bonding layer: setting the argon flow rate to 80-100 sccm, the chamber working pressure to 0.6-0.8 Pa, setting the high-power pulsed magnetron sputtering power source target voltage pulse width to 2-4 us, the peak power to 6-8 kW and the negative bias power supply to -30--100 V, the sputtering target to be Ti metal target, and the deposition time to 10-15 min; S5, preparation of TiN transition layer: set the argon flow rate to 60-80sccm, the nitrogen flow rate to 15-40sccm, the chamber working pressure to 0.6-0.8Pa, set the high-power pulsed magnetron sputtering power source target voltage pulse width to 2-4us, the peak power to 6-8kW and the negative bias power supply to -30--60V, the sputtering target material to be a Ti metal target material, and the deposition time to 10-15min; S6. Preparation of TiAlSiN nano-coating: the target material is TixAlySi(1-xy), the argon flow rate is set to 80-100sccm, the nitrogen flow rate is set to 20-40sccm, the chamber working pressure is set to 0.6-0.8Pa, the high-power pulsed magnetron sputtering power supply target voltage pulse width is set to 2-5us, the peak power is set to 6-8kW and the negative bias power supply is set to -60--100V, and the deposition time is set to 10-15min; S7 Sampling: Take samples 60 to 90 minutes after the coating preparation is completed.

[0007] Preferably, the glow cleaning process comprises: mounting the pre-treated workpiece sample on a sample stage, closing the vacuum chamber, and evacuating the vacuum chamber to 2×10 -4 Pa. Set the argon gas flow rate to 100-150 sccm, the chamber working pressure to 0.8-1.5 Pa, start the bias power supply to -600-800 V, and start glow cleaning for 90-120 minutes.

[0008] Preferably, the high-energy ion cleaning process includes: an argon gas flow rate of 100 to 120 sccm, a chamber working gas pressure of 0.6 to 0.8 Pa, a high-power pulsed magnetron sputtering power supply target voltage pulse width of 2 to 4 us, a peak power of 6 to 8 kW and a negative bias power supply of -100 to -150 V, a sputtering target material of a Ti metal target material, and an ion bombardment cleaning time of 10 to 15 min.

[0009] Preferably, the Ti bonding layer is prepared by deep oscillation magnetron sputtering technology, the working gas is argon, the gas pressure is 0.8-1.2 Pa, the substrate bias is -30--60 V, the sputtering power is 0.4-0.8 W, the micro-pulse parameter ton / toff=1-5 / 30-50 ms, and the thickness of the prepared Ti bonding layer is 50-100 nm; The Ti transition layer is biased to reduce residual stress. The bias control strategy is: -30V for 3 minutes, -100V for 3 minutes, -30V for 3 minutes, -100V for 3 minutes, -60V for 5 minutes. This bias control strategy makes the stress level lower, providing a higher film-substrate bonding strength for the subsequent coating preparation.

[0010] Preferably, the TiN transition layer is prepared by deep oscillation magnetron sputtering technology, the working gas is argon / nitrogen mixed gas, the gas pressure is 0.8 to 1.2 Pa, the substrate bias voltage is -30 to -60 V, the sputtering power is 0.4 to 0.8 W, and the micro-pulse parameter t on / t off =1~5 / 30~50ms, the thickness of the prepared TiN transition layer is 100~200nm; The TiN transition layer is bias controlled to reduce residual stress. The bias control strategy is: -30V preparation for 3 minutes, -60V preparation for 3 minutes, -30V preparation for 3 minutes, -60V preparation for 3 minutes, -100V preparation for 5 minutes; consistent with the low stress layer of the bonding layer, the microstructure is refined by high bias control.

[0011] Preferably, the TiAlSiN nano coating adopts deep oscillation magnetron sputtering technology composite pulse DC magnetron sputtering technology, the working gas is argon / nitrogen mixed gas, the gas pressure is 0.6 to 1.0 Pa, the substrate bias voltage is -60 to -100 V, the sputtering power is 0.6 to 1000 W, and the micro-pulse parameter t on / t off =1~5 / 30~50ms, and the thickness of prepared TiAlSiN is 0.5~1.0mm.

[0012] Preferably, the elemental compositions of Ti, Al, Si and N of the TiAlSiN nano-coating are 30-50 at.%, 5-10 at.%, 3-10 at.% and 50-55 at.% respectively; wherein the molar ratio N: (Ti+Al+Si)=1:1.

[0013] Preferably, in the preparation of the TiAlSiN nano-coating, the sputtering target is Ti and Ti x Al y Si (1-x-y) Alloy targets, including pulsed DC magnetron sputtering Ti targets, deep oscillation magnetron sputtering Tix Al y Si (1-x-y) , where x+y≤0.95, in Ti 0.77 Al 0.2 Si 0.03 When the Si content is ≤0.05, high bias voltage is used for regulation: -60V deposition for 5 minutes, then -100V deposition for 10 minutes.

[0014] The present invention provides a method for preparing a wear-resistant coating on the surface of a planetary ball screw. Compared with the prior art, it has the following beneficial effects: The wear-resistant coating prepared by the present invention has a thickness of about 1 to 2 mm, a nano-hardness of 35 to 55 GPa, H / E* (E* is the effective Young's modulus) ≥0.1, H3 / E*2≥0.3, film-base bonding strength (Rockwell indentation bonding strength ≥HF1), fracture toughness KIC≥3 MPa∙m1 / 2, and a friction coefficient ≤0.4; the wear-resistant coating has the characteristics of high strength and toughness integration, and the coating preparation has high uniformity, and the coating process is flexible and adjustable. In addition, the inner wall coating of the tube prepared by the method has a fast deposition rate, simple operation, low cost, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a scanning electron microscope image of the cross section of the nano coating on the surface of the screw rod of the present invention; Figure 2 is a graph showing the surface hardness of the coating of the present invention changing with depth; Figure 3 A schematic diagram of the Rockwell indentation bonding strength grade HF1 of the coating of the present invention; Figure 4 Schematic diagram of the Vickers indentation of the coating of the present invention; Figure 5 It is a parameter schematic diagram of the friction coefficient of the nano coating on the experimental substrate at the reciprocating friction frequency of 1 Hz and 2 Hz of the present invention. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] See also Figure 1-Figure 5 The present invention provides a method for preparing a wear-resistant coating on the surface of a planetary ball screw, which specifically comprises the following steps: S1. Cleaning of substrate: Place the lead screw workpiece in a commercial degreasing cleaning agent container for ultrasonic cleaning for 20 to 30 minutes, then clean it with deionized water for 5 to 10 minutes, and then dry it and place it for later use; S2. Substrate installation: Open the vacuum chamber, place the cleaned lead screw workpiece on the sample platform, close the door and evacuate until the vacuum degree is lower than 1×10-4Pa; S3, ion cleaning: cleaning by glow cleaning process and high energy ion cleaning process in sequence; The glow cleaning process includes: placing the pre-treated workpiece sample on the sample stage, closing the vacuum chamber, and evacuating the vacuum chamber to 2×10 -4 Pa. Set the argon flow rate to 100-150 sccm, the chamber working pressure to 0.8-1.5 Pa, start the bias power supply to -600-800 V, and start glow cleaning for 90-120 minutes; The high-energy ion cleaning process includes: argon gas flow rate of 100-120sccm, chamber working pressure of 0.6-0.8Pa, setting of high-power pulsed magnetron sputtering power source target voltage pulse width of 2-4us, peak power of 6-8kW and negative bias power supply of -100--150V, sputtering target material of Ti metal target material, and ion bombardment cleaning time of 10-15min; The Ti bonding layer is prepared by deep oscillation magnetron sputtering technology, the working gas is argon, the gas pressure is 0.8-1.2 Pa, the substrate bias is -30--60 V, the sputtering power is 0.4-0.8 W, the micro-pulse parameter ton / toff=1-5 / 30-50 ms, and the thickness of the prepared Ti bonding layer is 50-100 nm; The Ti transition layer is biased to reduce residual stress. The bias control strategy is: -30V for 3 minutes, -100V for 3 minutes, -30V for 3 minutes, -100V for 3 minutes. -60V for 5 minutes. This bias control strategy makes the stress level lower, providing a higher film-substrate bonding strength for the subsequent coating preparation. S4, preparation of Ti bonding layer: setting the argon flow rate to 80-100 sccm, the chamber working pressure to 0.6-0.8 Pa, setting the high-power pulsed magnetron sputtering power source target voltage pulse width to 2-4 us, the peak power to 6-8 kW and the negative bias power supply to -30--100 V, the sputtering target to be Ti metal target, and the deposition time to 10-15 min; S5, preparation of TiN transition layer: set the argon flow rate to 60-80sccm, the nitrogen flow rate to 15-40sccm, the chamber working pressure to 0.6-0.8Pa, set the high-power pulsed magnetron sputtering power source target voltage pulse width to 2-4us, the peak power to 6-8kW and the negative bias power supply to -30--60V, the sputtering target material to be a Ti metal target material, and the deposition time to 10-15min; S6. Preparation of TiAlSiN nano-coating: the target material is TixAlySi(1-xy), the argon flow rate is set to 80-100sccm, the nitrogen flow rate is set to 20-40sccm, the chamber working pressure is set to 0.6-0.8Pa, the high-power pulsed magnetron sputtering power supply target voltage pulse width is set to 2-5us, the peak power is set to 6-8kW and the negative bias power supply is set to -60--100V, and the deposition time is set to 10-15min.

[0018] S7 Sampling: Take samples 60 to 90 minutes after the coating preparation is completed.

[0019] In this embodiment, the TiN transition layer is prepared by deep oscillation magnetron sputtering technology, the working gas is argon / nitrogen mixed gas, the gas pressure is 0.8-1.2 Pa, the substrate bias voltage is -30--60 V, the sputtering power is 0.4-0.8 W, and the micro-pulse parameter t on / t off =1~5 / 30~50ms, the thickness of the prepared TiN transition layer is 100~200nm; The TiN transition layer is bias controlled to reduce residual stress. The bias control strategy is: -30V preparation for 3 minutes, -60V preparation for 3 minutes, -30V preparation for 3 minutes, -60V preparation for 3 minutes, -100V preparation for 5 minutes; consistent with the low stress layer of the bonding layer, the microstructure is refined by high bias control.

[0020] TiAlSiN nano-coating adopts deep oscillation magnetron sputtering technology and composite pulsed DC magnetron sputtering technology. The working gas is argon / nitrogen mixed gas, the gas pressure is 0.6~1.0Pa, the substrate bias voltage is -60~-100V, the sputtering power is 0.6~1000W, and the micro-pulse parameter t on / t off =1~5 / 30~50ms, the thickness of prepared TiAlSiN is 0.5~1.0mm.

[0021] The Ti, Al, Si and N element compositions of the TiAlSiN nano-coating are 30-50 at.%, 5-10 at.%, 3-10 at.% and 50-55 at.% respectively; wherein the molar ratio N: (Ti+Al+Si) is 1:1; and in the preparation of the TiAlSiN nano-coating, the sputtering target is Ti and Ti x Aly Si (1-x-y) Alloy targets, including pulsed DC magnetron sputtering Ti targets, deep oscillation magnetron sputtering Ti x Al y Si (1-x-y) , where x+y≤0.95, in Ti 0.77 Al 0.2 Si 0.03 When the Si content is ≤0.05, high bias voltage is used for regulation: -60V deposition for 5 minutes, then -100V deposition for 10 minutes.

[0022] Deep Oscillation Magnetron Sputtering (DOms) is a new type of high-power pulsed magnetron sputtering technology. Deep oscillation magnetron sputtering technology generates multiple sets of modulated voltage oscillation pulses, achieving stable high-power pulsed plasma discharge that completely eliminates arc discharge. This technology can achieve high target material ionization rate, high plasma density and high deposition rate, thereby significantly improving the comprehensive performance of deposited films.

[0023] Technical features: High target ionization rate: Through deep oscillation magnetron sputtering technology, target atoms can be ionized more effectively to form a high-density plasma.

[0024] High plasma density: This technology can generate a large amount of plasma in the sputtering area, providing sufficient raw materials for the deposition of thin films.

[0025] High deposition rate: Due to the high plasma density and high target ionization rate, the deposition rate of thin films is significantly increased.

[0026] Excellent film properties: Deep oscillation magnetron sputtering technology can produce films with high density, high hardness and good bonding strength.

[0027] Experimental Group: Select three ball screws of the same specification, set the numbers as 1#, 2# and 3# respectively, prepare the wear-resistant coating according to the above process, and measure and obtain the following parameters: Table 1. Mechanical properties and friction coefficient experimental table of Ti / TiN / TiAlSiN nano coating Sample No. Thickness (mm) Nanohardness (GPa) H / E* <![CDATA[H 3 / AND* 2 ]]> <![CDATA[Fracture toughness (MPa﹒m 1 / 2 )]]> Friction coefficient 1# 1.6 35.6 0.13 0.345 5.6 0.35 2# 1.8 44.5 0.12 0.331 4.5 0.32 3# 1.9 51.6 0.11 0.326 3.9 0.29 As shown in the table above, after more tests, it was determined that the thickness of the wear-resistant coating prepared by the present invention is about 1 to 2 mm, the nanohardness of the coating is 35 to 55 GPa, H / E* (E* is the effective Young's modulus) ≥0.1, H3 / E*2 ≥0.3, the film-base bonding strength (Rockwell indentation bonding strength ≥HF1), the fracture toughness K IC ≥3 MPa∙m1 / 2 , the friction coefficient is ≤0.4; the wear-resistant coating has the characteristics of high strength and toughness integration, and the coating preparation has high uniformity, and the coating process is flexible and adjustable. In addition, the screw rod surface coating prepared by this method has fast deposition rate, simple operation, low cost, and is suitable for mass production.

[0028] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0029] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0030] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a wear-resistant coating on the surface of a planetary ball screw, characterized in that: The specific steps include: S1. Cleaning of substrate: Place the lead screw workpiece in a commercial degreasing cleaning agent container for ultrasonic cleaning for 20 to 30 minutes, then clean it with deionized water for 5 to 10 minutes, and then dry it and place it for later use; S2. Substrate installation: Open the vacuum chamber, place the cleaned lead screw workpiece on the sample platform, close the door and evacuate the vacuum until the vacuum degree is lower than 1×10 -4 Pa; S3, ion cleaning: cleaning by glow cleaning process and high energy ion cleaning process in sequence; S4, preparation of Ti bonding layer: setting the argon flow rate to 80-100 sccm, the chamber working pressure to 0.6-0.8 Pa, setting the high-power pulsed magnetron sputtering power source target voltage pulse width to 2-4 us, the peak power to 6-8 kW and the negative bias power supply to -30--100 V, the sputtering target to be Ti metal target, and the deposition time to 10-15 min; S5, preparation of TiN transition layer: set the argon flow rate to 60-80sccm, the nitrogen flow rate to 15-40sccm, the chamber working pressure to 0.6-0.8Pa, set the high-power pulsed magnetron sputtering power source target voltage pulse width to 2-4us, the peak power to 6-8kW and the negative bias power supply to -30--60V, the sputtering target material to be a Ti metal target material, and the deposition time to 10-15min; S6. Preparation of TiAlSiN nano-coating: the target material is TixAlySi(1-xy), the argon flow rate is set to 80-100sccm, the nitrogen flow rate is set to 20-40sccm, the chamber working pressure is set to 0.6-0.8Pa, the high-power pulsed magnetron sputtering power supply target voltage pulse width is set to 2-5us, the peak power is set to 6-8kW and the negative bias power supply is set to -60--100V, and the deposition time is set to 10-15min; S7 Sampling: Take samples 60 to 90 minutes after coating preparation.

2. The method for preparing a wear-resistant coating on the surface of a planetary ball screw according to claim 1, characterized in that: The glow cleaning process includes: mounting the pre-treated workpiece sample on the sample stage, closing the vacuum chamber, and evacuating the vacuum chamber to 2×10 - 4 Pa, set the argon flow rate to 100-150 sccm, the chamber working pressure to 0.8-1.5 Pa, start the bias power supply to -600-800 V, and start glow cleaning for 90-120 minutes.

3. The method for preparing a wear-resistant coating on the surface of a planetary ball screw according to claim 1, characterized in that: The high-energy ion cleaning process includes: an argon gas flow rate of 100 to 120 sccm, a chamber working gas pressure of 0.6 to 0.8 Pa, setting a high-power pulse magnetron sputtering power supply target voltage pulse width of 2 to 4 us, a peak power of 6 to 8 kW and a negative bias power supply of -100 to -150 V, a sputtering target material of Ti metal target material, and an ion bombardment cleaning time of 10 to 15 minutes.

4. The method for preparing a wear-resistant coating on the surface of a planetary ball screw according to claim 1, characterized in that: The Ti bonding layer is prepared by deep oscillation magnetron sputtering technology, the working gas is argon, the gas pressure is 0.8-1.2 Pa, the substrate bias is -30--60 V, the sputtering power is 0.4-0.8 W, the micro-pulse parameter ton / toff=1-5 / 30-50 ms, and the thickness of the prepared Ti bonding layer is 50-100 nm; The Ti transition layer was bias controlled to reduce the residual stress. The bias control strategy was: -30 V for 3 min, -100 V for 3 min, -30 V for 3 min, -100 V for 3 min, and -60 V for 5 min.

5. The method for preparing a wear-resistant coating on the surface of a planetary ball screw according to claim 1, characterized in that: The TiN transition layer is prepared by deep oscillation magnetron sputtering technology, the working gas is argon / nitrogen mixed gas, the gas pressure is 0.8-1.2 Pa, the substrate bias voltage is -30--60 V, the sputtering power is 0.4-0.8 W, and the micro-pulse parameter t on / t off =1~5 / 30~50ms, the thickness of the prepared TiN transition layer is 100~200nm; The TiN transition layer was bias controlled to reduce the residual stress. The bias control strategy was: -30V preparation for 3 min, -60V preparation for 3 min, -30V preparation for 3 min, -60V preparation for 3 min, and -100V preparation for 5 min.

6. The method for preparing a wear-resistant coating on the surface of a planetary ball screw according to claim 1, characterized in that: The TiAlSiN nano coating adopts deep oscillation magnetron sputtering technology and composite pulse DC magnetron sputtering technology, the working gas is argon / nitrogen mixed gas, the gas pressure is 0.6-1.0 Pa, the substrate bias voltage is -60--100 V, the sputtering power is 0.6-1000 W, and the micro-pulse parameter t on / t off =1~5 / 30~50ms, the thickness of prepared TiAlSiN is 0.5~1.0mm.

7. The method for preparing a wear-resistant coating on the surface of a planetary ball screw according to claim 6, characterized in that: The TiAlSiN nano coating has Ti, Al, Si and N element compositions of 30-50 at.%, 5-10 at.%, 3-10 at.% and 50-55 at.% respectively; wherein the molar ratio N: (Ti+Al+Si)=1:

1.

8. The method for preparing a wear-resistant coating on the surface of a planetary ball screw according to claim 6, characterized in that: In the preparation of the TiAlSiN nano-coating, the sputtering target is Ti and Ti x Al y Si (1-x-y) Alloy targets, including pulsed DC magnetron sputtering Ti targets, deep oscillation magnetron sputtering Ti x Al y Si (1-x-y) , where x+y≤0.95, in Ti 0.77 Al 0.2 Si 0.03 When the Si content is ≤0.05, high bias voltage is used for regulation: -60V deposition for 5 minutes, then -100V deposition for 10 minutes.

Citation Information

Patent Citations

  • Preparation method for composite coating of cutter

    CN106756841A

  • Preparation technology of Si doped nano composite coating with ultrahigh hardness

    CN107190233A

  • TiAlSiN coating layer preparation method based on reactive sputtering hysteresis effect

    CN107227441A

  • Gradient nano coating for cutter, preparation equipment and method

    CN114381689A

  • Method for obtaining a multilayer thermodynamically stable wear-resistant coating (options)

    RU2759458C1

Cited By

  • Preparation method for self-lubricating composite material coating wound on shaft surface

    CN120402508A